SALMONELLA ABORTION IN SHEEP - Abduraimova, O. (Research Focus International Scientific Journal, 2026)
This article discusses and analyzes scientific literature on salmonellosis in farm animals in general, and salmonellosis-induced abortion in sheep in particular. It highlights the widespread prevalence and significant economic damage caused by salmonellosis not only in Uzbekistan but worldwide. The presence of other diseases that cause abortions in the sheep farming industry, along with the lack of specific clinical and other signs between them, creates significant challenges in establishing an accurate diagnosis.